Deficiency in Fpr2 results in reduced numbers of Lin(−)cKit(+)Sca1(+) myeloid progenitor cells - Chen, Keqiang (J Biol Chem, 2018)
The Lin(−)c-Kit(+) Sca-1(+) cell population in the bone marrow (BM) serves as the direct precursor for differentiation of myeloid cells. In this study, we report that deficiency in Fpr2, a G protein–coupled chemoattractant receptor in mice, is associated with reduced BM nucleated cells, including CD31(+)Ly6C(+) (granulocytes and monocytes), CD31(−)/Ly6C(int) (granuloid cells), and CD31(−)/Ly6C(high) (predominantly monocytes) cells. In particular, the number of Lin(−)c-Kit(+)Sca-1(+) (LKS) cells was reduced in Fpr2(−/−) mouse BM. This was supported by observations of the reduced incorporation of intraperitoneally injected bromodeoxyuridine by cells in the c-Kit(+) population from Fpr2(−/−) mouse BM. Purified c-Kit(+) cells from Fpr2(−/−) mice showed reduced expansion when cultured in vitro with stem cell factor (SCF). SCF/c-Kit-mediated phosphorylation of P38, STAT1, Akt (Thr-308), and Akt (Ser-473) was also significantly reduced in c-Kit(+) cells from Fpr2(−/−) mice. Furthermore, Fpr2 agonists enhanced SCF-induced proliferation of c-Kit(+) cells. Colony-forming unit assays revealed that CFU–granulocyte–macrophage formation of BM cells from Fpr2(−/−) mice was significantly reduced. After heat-inactivated bacterial stimulation in the airway, the expansion of c-kit(+) Sca-1(+) cells in BM and recruitment of Ly6G(+) cells to the lungs and CD11b(+)Ly6C(+)TNFα(+) cells to the spleen of Fpr2(−/−) mice was significantly reduced. These results demonstrate an important role for Fpr2 in the development of myeloid lineage precursors in mouse BM.